2010
DOI: 10.1177/0883073810370622
|View full text |Cite
|
Sign up to set email alerts
|

Are Incidental Findings on Brain Magnetic Resonance Images in Children Merely Incidental?

Abstract: The purpose of this study was to test the hypothesis that children with developmental delay without regression of unknown etiology are more likely to have intracranial incidental findings than are children with autistic spectrum disorder or children with normal development. Of 771 patients with magnetic resonance images, 363 (47.1%) patients had developmental delay, 55 (7.1%) had autistic spectrum disorders, and 353 (45.8%) were developmentally normal. Developmentally delayed children were more likely than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
1
15
2
Order By: Relevance
“…Medical imaging over the past several decades has sought to identify an anatomic biomarker for ASD, but one has yet to be found. In the search for such a biomarker, several neuroimaging studies reported incidental asymptomatic brain findings in children with ASD [Erbetta et al, 2013;Vasa et al, 2012;Gupta, Kanamalla, & Gupta, 2010;Boddaert et al, 2009;Zeegers et al, 2006;Taber et al, 2004;Brambilla et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Medical imaging over the past several decades has sought to identify an anatomic biomarker for ASD, but one has yet to be found. In the search for such a biomarker, several neuroimaging studies reported incidental asymptomatic brain findings in children with ASD [Erbetta et al, 2013;Vasa et al, 2012;Gupta, Kanamalla, & Gupta, 2010;Boddaert et al, 2009;Zeegers et al, 2006;Taber et al, 2004;Brambilla et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…The range of normal variation includes structural anomalies that are traditionally considered as clinically, neurologically, and neuropsychologically asymptomatic. The incidence of these anomalies ranges widely, from 4% to 80%, when including samples drawn retrospectively from clinical cases with MRI whose diagnoses were ultimately deemed non-serious (Gupta and Belay 2008; Bredlau et al 2012; Famini et al 2011; S. Gupta et al 2010; Potchen et al 2013; Roth et al 2012) and, not surprisingly, was substantially higher in the elderly (Morris et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, children with developmental delay of unknown etiology, according to retrospective chart reviews, were more likely (1.8 odds ratio) to have incidental findings than healthy control subjects. 7 In a recent meta-analysis, Trzesniak et al 8 concluded that the presence of a large cavum septum pellucidum is associated with schizophrenia spectrum disorders. However, no study has examined whether a finding of cavum septum pellucidum in an epidemiologically accrued sample is associated with increased incidence of psychotic features.…”
mentioning
confidence: 99%